BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU BERISIKO KONSUMSI MAKANAN FAST FOOD - El Zenitia Villa Rinjani; Dewi Candra Resmi; Seniwaty Anwar; Noviana Hikmawati (Ensiklopedia Research and Community Service Review, 2026)
Abstract: Adolescents’ eating patterns have undergone significant changes, one of which is marked by an increase in the consumption of fast food. Based on a preliminary survey conducted through interviews with students at a high school in Surabaya, it was found that 100% of the students were aware of the dangers of consuming fast food but still preferred it over other types of food. The purpose of this study was to identify several factors associated with the risky behavior of consuming fast food. A cross-sectional study design was used. The study was conducted at a high school in Surabaya in September 2025. The sample consisted of 80 participants. Stratified random sampling was used. The research instrument used was a questionnaire. Data analysis was performed using univariate and bivariate methods. The results indicated an association between the influence of peers (p-value: 0.023) and allowance (p-value: 0.016) and fast-food consumption behavior. It is recommended that schools collaborate to establish a health organization directly supervised by the community health center to introduce educational programs on balanced eating habits. For students who tend to consistently choose fast food, it is important to educate them on the importance of a healthy diet.Keywords: Fast Food, Teens, Pocket Money.